Urgensi Tes Kesehatan HIV/AIDS sebagai Syarat Pra Nikah di Indonesia - Pratiwi, Charine alya; Radliyah, Nunung; Zazili, Ahmad (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
Premarital HIV testing has emerged as a crucial preventive strategy in reducing the transmission of HIV/AIDS, particularly within the context of marital relationships in Indonesia. Despite rising HIV cases and the potential for intra-marital transmission, implementation of mandatory HIV testing for prospective spouses remains inconsistent across regions. This study aims to analyze the urgency and implications of premarital HIV testing as a marriage requirement in Indonesia, focusing on regulatory frameworks, practical implementation, and human rights considerations. A normative juridical method is employed, supported by a conceptual approach and literature review, alongside interviews with selected stakeholders including health officials and couples who have undergone testing. The findings reveal that although regional regulations mandate such testing, several challenges persist: limited healthcare infrastructure, insufficient public awareness, and social resistance rooted in stigma and misconceptions. Moreover, while premarital HIV testing serves public health interests, it also raises ethical concerns regarding privacy, consent, and potential discrimination. If supported by clear policies, adequate counseling, and strong confidentiality measures, premarital HIV testing can effectively safeguard public health without infringing on individual rights. This study recommends reinforcing inter-agency coordination, expanding access to voluntary and informed testing, and designing rights-sensitive policies that balance public health priorities with individual autonomy.